Medios de comunicación de Iberoamérica en la Web Caso Uruguay - Montesdeoca Abad,Elizabeth Marianela (2018)
Abstract:This paper analyzes the information architecture of the websites of digital media in Ibero-America, in this case, Uruguay. The research was carried out through a sample of eight media: El País, El Observador, Teledoce, Subrayado, El Espectador, Radio Uruguay, Montevideo Portal and La Red 21. These media belong to the traditional sectors: television, radio, press including to the digital natives. Through content analysis sheets, and online tools such as Alexa, Whois, Internet Archive and TAWdis, information was extracted from the media in terms of accessibility, constant updating, hypertextuality, multimedia, interactivity, usability, application of new trends in journalism, and the presence in social networks and the use of external platforms as content support. The results suggest that digital media should reinforce the use of Web 2.0 tools, as well as venture into new trends in journalism.